Development of Underwater Motion Capture System for Space Suit Mobility Assessment. (September 2017) - Bernal, Yaritza; Kim, K. Han; Benson, Elizabeth; Jarvis, Sarah; Harvill, Lauren; Meginnis, Ian; Rajulu, Sudhakar
The objective of this study was to develop and deploy a novel motion capture system that utilizes off-the-shelf, dive-rated hardware to measure 3-D whole body reach envelopes of space suits in an underwater analog, which simulates a microgravity environment. The accuracy of the developed system was compared to a gold standard motion capture system in a dry-land condition before deployment. This study is ultimately aimed at providing a methodology for quantitative metrics to evaluate and compare the mobility performances of a newly developed prototype space suit versus an existing space suit at the Neutral Buoyancy Laboratory (NBL) at NASA's Johnson Space Center.